LIQUID CRYSTAL DISPLAY DEVICE - YAMADA YUMIKO (1999)
PROBLEM TO BE SOLVED: To make a liquid crystal display device high in aperture ratio and improved in picture quality by providing a reflector having a random ruggedness on a surface opposed to a substrate, first electrode oppositely arranged on the random rugged surface between the substrate and the reflector, and a second electrode placed opposite to the first in the manner of covering it through an insulating film. SOLUTION: A storage capacity auxiliary electrode 8 is electrically connected to a pixel electrode 10 in a contact hole provided in an inter-layer insulating film 11, with an auxiliary capacity formed between it and the auxiliary capacity line 5. In other words, the ruggedness of the pixel electrode 10 is formed by that of the inter-layer insulating film 11; each recessed part of the pixel electrode 10 positioned on the auxiliary capacity line 5 is brought into contact with the storage capacity auxiliary electrode 8, by means of the contact hole provided in this inter-layer insulating film 11, with the auxiliary electrode 8 electrically connected to the pixel electrode 10. The flat part on the TFT area of this inter-layer insulating film 11 is also formed with a light shielding film 12 made of a black resin. In addition, a columnar spacer 13 is arranged on the light shielding film 12 in the TFT area.